Structure activity study of S-trityl-cysteamine dimethylaminopyridine derivatives as SIRT2 inhibitors: Improvement of SIRT2 binding and inhibition. Issue 19 (1st October 2020) - Radwan, Mohamed O.; Ciftci, Halil I.; Ali, Taha F.S.; Koga, Ryoko; Tateishi, Hiroshi; Nakata, Akiko; Ito, Akihiro; Yoshida, Minoru; Fujita, Mikako; Otsuka, Masami
Graphical abstract: Abstract: Sirtuin proteins are a highly conserved class of nicotinamide adenine dinucleotide (NAD + )-dependent lysine deacylases. The pleiotropic human isoform 2 of Sirtuins (SIRT2) has been engaged in the pathogenesis of cancer in a plethora of reports around the globe. Thus, SIRT2 modulation is deemed as a promising approach for pharmaceutical intervention. Previously, we reported S -Trityl-l -Cysteine (STLC )-ornamented dimethylaminopyridine chemical entity named STC4 with a significant SIRT2 inhibitory capacity; this was separate from the conventional application of STLC scaffold as a kinesin-5 inhibitor. An interactive molecular docking study of SIRT2 and STC4 showed interaction between Asn168 of SIRT2 and the methyl ester of STC4, that appears to hinder STC4 to reach the selective pocket of the protein unlike strong SIRT2 inhibitor SirReal2 . To improve its activity, herein, we utilized S -trityl cysteamine pharmacophore lacking the methyl ester. Nine compounds were synthesized and assayed affording three biopertinent SIRT2 inhibitors, and two of them, STCY1 and STCY6 showed higher inhibitory activity than STC4 . These compounds have pronounced anti-proliferative activities against different cancer cell lines. A molecular docking study was executed to shed light on the supposed binding mode of the lead compound, STCY1, into the selective pocket of SIRT2 by interaction of the nitrogen of pyridine ring of the compound and Ala135 of the protein. The outcome of the study exposes that the active compounds are effective intermediates to construct more potent biological agents.